Pengaruh Kombinasi Relaksasi Benson dan Slow Deep Breath Terhadap Intensitas Nyeri Post Operasi Sectio Caesarea di RSAB Harapan Kita Jakarta - Mahmudi Mahmudi; Ratna Sari Dinaryanti (Poltekkes Kemenkes Padang, 2022)
Postoperative pain is still one of the problems in nursing care, there are many therapies that can be done to reduce pain. One of the non-pharmacological actions is relaxation. Relaxation is a technique that relaxes the mind and body through a process that will progressively release muscle tension. The purpose of this study was to determine the effect of the combination of Benson's relaxation therapy and slow deep breath on the pain intensity of postoperative sectio caesarea patients. The research design used “ Quasy Experiment ” one group pre post test design without control. Samples were all post sectio caesaria pain patients in RSAB Harapan Kita Jakarta using purposive sampling method as many as 18 patients. Collecting data by interview and direct observation using the standard pain value Numeric Rate Scale. Analysis of the data using the Dependent T test . The results showed the mean value before the combination of Benson relaxation therapy and slow deep breath was 4.72 and the mean value after therapy was 3.00. So that the combination of Benson relaxation theraphy and slow deep breath can reduce the intensity of pain in patients post section caecaria with p value 0,0000. With this study, it is expected that the combination of Benson relaxation therapy and slow deep breath can be used as an non-pharmacology intervention to reduce pain in patients post operation sectio caecaria.